2010
DOI: 10.1016/j.expneurol.2009.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sympathetic outflow on upregulation of vanilloid receptors TRPV1 in primary afferent neurons evoked by intradermal capsaicin

Abstract: The vanilloid receptor TRPV 1 is a key nociceptive molecule located in primary afferent nociceptive neurons in dorsal root ganglia (DRG) for initiating neurogenic inflammation and pain. Our recent study demonstrates that up-regulation of TRPV 1 receptors by intradermal injection of capsaicin is modulated by activation of the protein kinase C (PKC) cascade. Neurogenic inflammation and pain resulting from capsaicin injection are sympathetically dependent, responding to norepinephrine, adenosine 5′-triphosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 78 publications
(163 reference statements)
0
20
0
Order By: Relevance
“…Mechanically insensitive heat nociceptors express TRPV1 (Lawson et al, 2008) and release neuropeptides via local axon reflex that are involved in heat-induced vasodilation (Cavanaugh et al, 2011; Magerl and Treede, 1996; Rukwied et al, 2007; Xu et al, 2010). However, simply activating TRPV1 in these cells via brief noxious heat application by itself did not convert 'silent' afferents, indicating that heat and local vasodilation play a largely permissive role.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically insensitive heat nociceptors express TRPV1 (Lawson et al, 2008) and release neuropeptides via local axon reflex that are involved in heat-induced vasodilation (Cavanaugh et al, 2011; Magerl and Treede, 1996; Rukwied et al, 2007; Xu et al, 2010). However, simply activating TRPV1 in these cells via brief noxious heat application by itself did not convert 'silent' afferents, indicating that heat and local vasodilation play a largely permissive role.…”
Section: Discussionmentioning
confidence: 99%
“…A stronger correlation was observed between the CPM-mediated increase in histaminergic neurogenic inflammation and the CPM-induced increase in skin conductance at the fingertips indicating that activity of efferent sudomotor fibers (tightly associated with sympathetic vasoconstrictor fibers) predicts CPM-induced neurogenic flare aggravation. This notion is theoretically supported by several animal studies wherein sympathectomy and pharmacological blockade of sympathetic efferent results in greatly diminished neurogenic inflammatory responsiveness (Levine et al 1986;Wang et al 2004;Xu et al 2010). Of particular interest, it has been shown that capsaicin-induced neurogenic flare in mice was dependent on sympathetic efferents by an indirect mechanism acting on peripheral a 1 -adrenoceptors, hereby augmenting sensitization of sensory afferents known to produce neurogenic inflammation (Ali et al 1999;Wang et al 2004).…”
Section: The Neurogenic Inflammatory Response Is Increased By Heterotmentioning
confidence: 89%
“…Recent research has shown that sympathetic denervation signifi cantly reduces the CAP-evoked expression of tran- sient receptor potential vanilloid type 1 and sensory neuropeptide calcitonin gene-related peptide [21] . This suggests that sympathetic noradrenergic modulation is implicated in CAP-evoked pain sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the α1-adrenoreceptor agonist phenylephrine causes the release of SP from terminals of CAP-sensitive sensory neurons in the lumbar enlargement of the dorsal spinal cord and urinary bladder [5] . Neurogenic infl ammation and pain resulting from CAP injection respond to NA released from sympathetic efferents [21] .…”
Section: Introductionmentioning
confidence: 99%